AN INFRARED-LUMINOUS MERGER WITH TWO BIPOLAR MOLECULAR OUTFLOWS: ALMA AND SMA OBSERVATIONS OF NGC3256 - Sakamoto, Kazushi; Aalto, Susanne; Combes, Francoise; Evans, Aaron; Peck, Alison (The Astrophysical journal, 2014)
We report Atacama Large Millimeter/sub-millimeter Array and Submillimeter Array observations of the infrared-luminous merger NGC3256, the most luminous galaxy within z = 0.01. The northern nucleus is more massive and is surrounded by molecular spiral arms. Its nuclear disk is face-on, while the southern nuclear disk is almost edge-on. The high-velocity molecular gas in the system can be resolved into two molecular outflows from the two nuclei. The one from the northern nucleus is part of a star-burst-driven super-wind seen nearly pole-on. The sum of these outflow rates, although subject to the uncertainty in the molecular mass estimate, either exceeds or compares to the total star formation rate. The feedback from nuclear activity through molecular outflows is therefore significant in the gas consumption, and hence evolution, of this system.